Study of some economic and political factors on the exchange rate of the Iraqi dinar during the period (2004-2018) - Iman Ibrahim Ismail; Mardin Mahsum Faraj; Ahmed Taha Bilal (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This study aimed at identifying the economic and non-economic factors that affect the exchange rate of the Iraqi dinar during the period (2004-2018). Through this research, the impact of (foreign currency auction, money supply, global financial crisis,) on the exchange rate of the Iraqi currency, The model was estimated using the OLS method, ARDL. Of the results reached, it turns out that the auction of foreign currency contributed to the decline in the exchange rate Iraqi dinar, and the impact of the presentation of cash (M1) negative on the exchange rate Iraqi dinar, While the effect of the presentation of cash (M2) on the exchange rate of the Iraqi dinar in current periods and previous periods, so that the impact of the current period was positive in the sense that the increase in money supply contributed to the high exchange rate of the Iraqi dinar, while the impact of the presentation of cash in the previous period ( LM2(-1)) was negative and contributed to the deterioration of the exchange rate of the Iraqi dinar Despite the importance of internal and global conditions and regional but the impact on the exchange rate of the Iraqi dinar was not of statistical significance.This study concluded the need to achieve a balance between the monetary sectors And real by a balanced fit of the mass and the GDP.